Analisis I-E (Internal-Eksternal) Matriks dan Strategic Position and Action Evaluation (Space) dalam Pengembangan Usaha Nugget Ikan - Alfianar, Dewi Robihat; Simatupang, David Oscar; Widiastuti, Maria Maghdalena Diana (MuJAgri: Musamus Journal of Agribusiness, 2020)
This research aims to identify the factors of strengths, weakness, opportunities and the threat. The formulation of bussiness development strategy of fish nuggets uses SWOT analysis and descriptive qualitative methods. This research is conducted in Maro and Samkai villages, Merauke district for two months from May to June 2016. The results of this research generate strategies for business expansion of fish nuggets products. The strategy (startegis) is (are) to optimize human resources of all members on from processing to marketing that build good communication; to conduct training for group members to increase the quality of human resources; to improve the manner of marketing, quantity product and consumer confidence to buy fish nuggets products; toincrease the supply of raw materials to optimize the fish nuggets production continuously;m to find the investor for increasing the capital; to submitte a proposal to the government or related institutions; to build an important promotion for enlarge the market of fish nuggets through the brochures, leflet, web, newspaper, and others medias.